Time to Oncological Surgery: Impact of Treatment Delays on Tumor Progression, Clinical Outcomes, and Healthcare Efficiency - Ivana Cárdenas Ayala; Heriberto Inclán Figueroa; Pedro Aníbal Bailón de la O; Jaime Héctor Cisneros Sandoval; Diego Clemente Moreno; Pablo Eduardo Navarro López; Aldo Bolivar Zavala Segovia; Andrea Delgado Cardona (IECCMEXICO, 2026)
Delays between cancer diagnosis and definitive oncological surgery have become an increasingly relevant concern due to their potential impact on tumor progression, clinical outcomes, and healthcare efficiency. This study analyzed available evidence regarding the relationship between surgical waiting times and oncological outcomes in adult patients with solid tumors, with particular emphasis on breast, colorectal, lung, pancreatic, bladder, and head and neck cancers. A structured integrative review was conducted using the Scientific Method, incorporating systematic reviews, meta-analyses, population-based studies, and observational cohorts. The analysis focused on time from diagnosis to surgery, overall and disease-specific survival, pathological upstaging, recurrence, resectability, postoperative outcomes, treatment complexity, and healthcare-related factors. The findings showed that prolonged and avoidable delays were generally associated with less favorable outcomes, although the magnitude of the effect varied according to tumor type, stage, biological aggressiveness, and treatment sequence. Across several surgical indications, each additional four-week delay was associated with an approximate 6–8% increase in mortality hazard, while specific studies also demonstrated greater pathological upstaging, reduced long-term survival, and loss of surgical opportunity with extended waiting periods. Organizational factors, including limited surgical capacity, interinstitutional transfers, diagnostic bottlenecks, and administrative processes, contributed to treatment delays and may increase resource utilization and therapeutic complexity. The results support the need to distinguish clinically justified waiting periods from avoidable postponements and highlight the importance of tumor-specific, risk-adapted surgical prioritization. Timely oncological surgery should therefore be considered an integral component of cancer care quality, with potential benefits for survival, disease control, healthcare efficiency, and equity.